How Unified Is the European Union? European Integration Between Visions and Popular Legitimacy - Gustavsson, Sverker; Oxelheim, Lars; Pehrson, Lars (Springer Berlin Heidelberg : Imprint: Springer, 2009)
The European project has come a long way in establishing peace, creating a common market, and expanding its borders. At the same time, diminishing popular legitimacy has spurred talk about a European Union in crisis. How far has the EU really come in fulfilling its grand visions? Is the project barely half-way? Or could we say with some confidence that European integration is solidified and will continue to get stronger? This book brings together contributors from economics, political science and law to offer different perspectives on this larger issue. The questions asked include: How far has the European Union come in its creation of a Common Foreign and Security Policy? What will happen to the state monopolies? Is there a common strategy at the European level for integrating immigrants? To what extent do national political parties cooperate with the Europarties? By investigating these and similar issues the book contributes to an assessment of how successful European integration has been to date. .